Operative and Postoperative Complications of Laparoscopic Cholecystectomy: Experience from a Tertiary Care Hospital of Bangladesh - Maitra, Tapash Kumar; Ullah, Mahmud Ekram; Faruquzzaman, -; Mondol, Samiran Kumar (Bangladesh Critical Care Journal, 2017)
Background: The technique of laparoscopic surgery has rapidly become popular because of its several advantages over conventional open surgery. The reduction of postoperative pain provided positive human impact, and the reduction of length of hospital stay as well as the earlier return to work generated a positive socioeconomic impact. However, in spite of being a minimally invasive technique, this procedure has different peroperative and postoperative complications which cannot be disregarded. Objective: To evaluate the complications of laparoscopic cholecystectomy in symptomatic and asymptomatic cholelithiasis and other benign gall bladder diseases. Methodology: 172 patients who underwent laparoscopic cholecystectomy were included in this prospective study on the basis of non-randomized convenient sampling from a period of September 30, 2014 to September 30, 2016 in BIRDEM General Hospital, Dhaka, Bangladesh. Data of the patients regarding outcomes and complications were analyzed. Result: Results of this study suggests that 35.5% cases were male and 64.5% patients were female. In male group, most of the patients (18.0%) were in 41-50 years of age group followed by 9.9% in 51-60 years age group, whereas among the female patients these were 33.1% and 15.7% respectively. Mean±SD of age were46±1.7 and 42±1.3 years in case of male and female patients respectively.In 119 (69.2%) out of total 172 cases, laparoscopic cholecystectomy was done for chronic cholecystitis and in 18.6% (32 out of total 172) cases, it was performed for acute cholecystitis. Intra-operative bile leak(11.0%) was found to be the most frequent complications during laparoscopic cholecystectomy. The incidence rates of perforation of gall bladder, stone spillage were 9.3% and 5.2% respectively. Trocar site, vascular, and hepatic bed hemorrhages were 7.0%, 4.7% and 4.0% respectively. Open conversion was done in 17 cases (9.9%). Port site infection and post cholecystectomy syndrome developed in 5.2% and 4.7% cases respectively. The overall mortality was approximately 1.1%. Serious complications likebowel injury and bile duct injury were recorded in 0.6% and 1.2% cases respectively.The results of this study suggest that gender, age, co-morbidities, previous abdominal surgery, acute cholecystitis, obesity, thickened gall bladder wall on ultrasound, history of preoperative ERCPare probablyimportant and clinically significant relevant factors for open conversion of laparoscopic cholecystectomy. Conclusion: In our study, complications of laparoscopic cholecystectomy were similar to those of different centres in western countries. We found laparoscopic cholecystectomy as a safe and effective procedure in almost all patients with cholelithiasis. Proper preoperative work up, awareness of possible complications and adequate training on laparoscopic technique make this operation a safe procedure with favorable result and lesser complications. Bangladesh Crit Care J March 2017; 5(1): 11-16